Endothelial adenosine A2a receptor-mediated glycolysis is essential for pathological retinal angiogenesis - Zhiping Liu (Nature Portfolio, 2017)
Pathological angiogenesis in the retina is a major cause of blindness. Here the authors show that adenosine receptor A2A drives pathological angiogenesis in the oxygen-induced retinopathy mouse model by promoting glycolysis in endothelial cells via the ERK/Akt/HIF-1α pathway, thereby suggesting new therapeutic targets for disease treatment.